Effects of the Lysulin™ supplementation on pre-diabetes: A randomized double-blind, placebo-controlled clinical trial. Issue 5 (September 2020) - Ranasinghe, Priyanga; Jayawardena, Ranil; Chandrasena, Lal
Abstract: Background and aims: Diabetes is a leading cause of morbidity and mortality worldwide. Recent studies have demonstrated that nutraceutical products have beneficial effects in diabetes. Present study aims to investigate whether a product (Lysulin™) containing amino acid lysine, micronutrient zinc and vitamin C will have beneficial effects in pre-diabetes. Methods: A randomized, double-blind, placebo-controlled trial was conducted for a period of 6 months. The two parallel groups (1:1) were Lysulin™ (Interventional group–IG) and placebo (control group–CG). Evaluations were done at baseline, 1, 3 and 6 months. Primary outcome was defined as change in glycaemic control measured by HbA1c from baseline. Other outcomes included change in; fasting plasma glucose (FPG), 2-h OGTT plasma glucose and lipid profile from baseline. Three multiple regression analyses were performed, where change in FPG, 2-h OGTT, and HbA1c post intervention from baseline respectively were the continuous dependent variable with other independent variables. Results: One hundred and ten participants were recruited, 50% (n = 55) were males and mean age (±SD) was 46.7 ± 9.9 years. A significantly higher percentage of participants in CG (25.4%, n = 14) developed diabetes in comparison to IG (7.3%, n = 4) (p = 0.018). FPG, 2-h OGTT and HbA1c significantly reduced in the IG only. Both total cholesterol and LDL cholesterol decreased significantly from baseline only in the IG. In all three regression models the best predictor of respective dependent variable was Lysulin™ treatment. Conclusions: Lysulin™ improved glycaemic control, with reduced progression to diabetes, in those with pre-diabetes. Treatment also showed a beneficial reduction in total and LDL cholesterol levels. Trial registration: Sri Lanka Clinical Trials Registry, identifier: SLCTR/2018/022 (http://slctr.lk/trials/1290 ). Registered on 13th July 2018; Study protocol version 2.0 (23rd March 2018). Highlights: Lysulin™ is a nutraceutical containing essential amino acid lysine, vitamin C and micronutrient zinc. It improved glycaemic control, with reduced progression to diabetes, in those with pre-diabetes. Other benefits include the reduction in total and LDL cholesterol.